Phytochemical screening and antimicrobial activity of plant leaf extract against enteric bacterial pathogens - Murali, Uthamalingam; Pandeeswari, N.; Elango, Boojhana; Murugesan, Karthikeyan; Abirami, K.; Divya, V. V.; Sathya, T. A.; Basalingappa, Kanthesh M.; Mathanmohun, Maghimaa (Journal of Medicinal Herbs and Ethnomedicine, 2023)
Punica granatum, a fruit-bearing shrub belonging to the Lythraceae family, offers various benefits to humans, with both its fibers and seeds being valuable. The seeds contain important oil acids such as palmitic, punica, stearic, and oleic acids. In India, P. granatum (pomegranate) leaves have been investigated for their potential antibacterial activity against enteric pathogens. These pathogens are responsible for causing gastrointestinal infections and are often associated with antibiotic resistance. The study aims to explore whether pomegranate leaves possess properties that can combat these enteric pathogens effectively. This research holds promise in identifying a natural and alternative approach to address antibacterial challenges, potentially contributing to the development of novel antimicrobial agents pomegranate is commonly used as a traditional remedy for treating enteric bacterial pathogens. To investigate its antibacterial properties, researchers studied the aqueous extract of P. granatum leaf against enteric pathogens, conducting tests like biochemical examinations and microscopy on the isolates. The phytochemical analysis of P. granatum (pomegranate) leaf aqueous extract revealed the presence of various bioactive compounds. These compounds include amino acids, carbohydrates, alkaloids, steroids, flavonoids, terpenoids, saponins, tannins, and phenols. To evaluate its antimicrobial activity, the researchers used antibiotic discs, including chloramphenicol, vancomycin, and gentamicin, employing the standard Kirby Bauer method. Results showed that vancomycin had the highest zone of inhibition, followed by chloramphenicol and gentamicin, with respective measurements of 20 mm and 19 mm. Chloramphenicol exhibited sensitivity against Escherichia coli (19 mm), while gentamicin showed sensitivity against Salmonella typhi (20 mm), Staphylococcus aureus (19 mm), and E. coli (18 mm). Vancomycin demonstrated sensitivity against S. aureus (21 mm). The aqueous leaf extract displayed significant antibacterial activity at concentrations of 20, 40 mcg, and 60 μg, showing effective zones of inhibition ranging from 15 mm to 22 mm against Pseudomonas aeruginosa, E. coli, S. aureus, Shigella dysentriae, Proteus vulgaris, and S. typhi. In conclusion, the study established that P. granatum leaf extracts possess remarkable antibacterial properties and contain valuable pharmaceutical bioactive compounds. Due to its efficacy in treating gastrointestinal disorders, it is utilized as a natural remedy in traditional medicine.